Metal Nanostructure Synthesis via Surface Energy Driven Growth - Boland, John (My University, 2016)
Identifying new synthesis methods to produce single crystal metal nanowires has the potential to expand nanowire based technology integration and increase applications. The catalogue of single crystal metal nanostructures is rather limited compared to the range of high aspect semiconductor nanowires synthesized via well-established vapor liquid solid and atomic layer deposition methods. The surface energy driven growth (SEDG) method opens new possibilities for producing novel metal nanostructures. The method, based on the relative surface energy of the components involved in the synthesis is presented as a standalone method for producing high aspect ratio single crystal metal nanowires. Wire growth is realized following eutectic temperature annealing of individual thin films that make up binary alloy systems. In response to thermal annealing the high surface energy component is observed to crystallize and form wire structures directly form the bilayer material without the introduction of growth precursors. The potential of this growth method has been demonstrated in the several recent examples of nanostructures synthesized using SEDG. Focus here will be on generalizing the method to enable future synthesis via this new method. Controlled positioning of the growth can be achieved through manipulation of dewetting phenomena to control mass flow and facilitated by the placement of defects that nucleate the de-wetting phenomenon. The physical principles dictating the growth method are covered in detail to enable fine control over positioning and dewetting during growth. The principles of the method are presented together in detail for the first time with the aim of increasing the accessibility of the method for the wider scientific community.
Keywords: Metal nanowire; metal synthesis; single crystal; SEDG; agglomeration; crystallization